Self-Awareness, Power Relations, and Strategies to Prevent Sexual Violence in Islamic Boarding Schools: A Literature Review - Hazimatul Layyinah; Zarina Akbar; Ratna Dyah Suryaratri (International Conference on Psychology and Education (ICPE), 2025)
In Islamic boarding schools, students are typically nurtured within a hierarchical environment, making self-awareness crucial for distinguishing between healthy obedience and harmful submission. Unequal power relationships between caregivers and students often become the root cause of sexual violence cases, thus preventive efforts must carefully consider these power dynamics. This study aims to examine the role of self-awareness as a protective factor for students, understand the influence of power relations in the occurrence of violence, and review preventive strategies that have been implemented in Islamic boarding school settings. This review analyzed 15 national and international articles published between 2016 and 2025, using quantitative, qualitative, and literature review approaches. The findings indicate that self-awareness plays a significant role in enhancing students’ ability to recognize the risks of sexual violance; however, its effectiveness is influenced by existing power imbalances that often silence victims. Effective preventive strategies identified include religiously grounded sex education, peer counselor training, parenting interventions, and the implementation of internal regulations within Islamic boarding schools.